Description of two new Isophya taxa (Orthoptera: Tettigonioidea: Phaneropteridae) from Serbia - Pavićević, Dragan (Biologia Serbica, 2021)
During field work conducted over the past few years, the author has found two new taxa of the bush cricket genus Isophya in Serbia, I. modesta danubiensis ssp. n. in Tumane near Golubac (eastern Serbia) and I. modestior grebenschikovi n. ssp. in Belgrade, Miljakovac and Mt. Avala. Comparisons were made by nominal taxa I. modesta modesta from Romania (Mehadia) and I. modestior modestior from the environs of Niš. The morphology of the new taxa, scanning electron microscope images of male stridulatory files, as well as ecology and phenology are presented.